The Eclipse of Equality in a World of Extremes - Hooton, Peter (International journal of public theology, 2022)
Christianity and democracy have in common the idea of equality before God and the law. But how seriously was this notion taken by the Christian architects of modern representative democracy, and how seriously is it taken in today’s deeply unequal democratic societies? Democracy has long embraced the idea of a formal equality of persons but has generally held substantive equality to be incompatible with the secure possession of private property, which is its overriding priority. This article explores the relationships of Christianity and democracy to property and wealth, and the ever-present tension in both between less and more rigorous forms of each. Christianity and democracy are for many people little more than identity markers, but their survival as robust and relevant approaches to social life depends on a vision – which includes Christ’s teachings on renunciation and democracy’s egalitarian ethos – underlying the forms.